Effect of the Pore Size Distribution on the Displacement Efficiency of Multiphase Flow in Porous Media - Yang Yongfei (Open Physics, 2016)
Due to the complexity of porous media, it is difficult to use traditional experimental methods to study the quantitative impact of the pore size distribution on multiphase flow. In this paper, the impact of two pore distribution function types for three-phase flow was quantitatively investigated based on a three-dimensional pore-scale network model. The results show that in the process of wetting phase displacing the non-wetting phase without wetting films or spreading layers, the displacement efficiency was enhanced with the increase of the two function distribution’s parameters, which are the power law exponent in the power law distribution and the average pore radius or standard deviation in the truncated normal distribution, and vice versa. Additionally, the formation of wetting film is better for the process of displacement.